(untitled) (International journal of artificial intelligence, 2026)
This article analyzes pedagogical strategies aimed at preventing students from misusing Large Language Models (LLMs) in ways that violate the principles of academic integrity. In recent years, the widespread adoption of artificial intelligence–based tools has brought new opportunities to the educational process, while also creating various risks and challenges. In particular, students increasingly tend to use LLM services as a direct solution instead of developing skills such as independent creative thinking, academic writing, and conducting research. This has led to the emergence of new forms of plagiarism and a decline in the quality of education (Chan, 2023; Prokhorova et al., 2024; Lund et al., 2025). Therefore, educators are required to adopt modern, technology-oriented pedagogical approaches. The article identifies the main causes of illegal or unethical use of LLMs, including excessive academic workload, insufficient time-management skills, lack of motivation caused by monotonous assignments, weak assessment mechanisms and the absence of a digital responsibility culture among students. Alongside this, the study highlights effective pedagogical strategies for addressing the issue: regular promotion of academic integrity, designing creative, contextual, and personalized assignments, organizing instructional sessions on ethical and proper use of LLMs, implementing multi-stage assessment practices (draft submissions, oral defense, reflection), encouraging collaborative learning, and fostering an atmosphere of pedagogical trust and openness rather than relying solely on AI-detection tools (Ardito, 2025; Lund et al., 2025).